Astrocytic Calcium Signaling Toolkit (astroCaST): efficient analysis of dynamic astrocytic calcium events - Reising, Jan Philipp; Gonzalez-Sanchez, Ana Cristina; Samara, Athina; Herlenius, Eric (Frontiers in Cellular Neuroscience, 2024)
The Astrocytic Calcium Signaling Toolkit (astroCaST) is a novel solution to a longstanding challenge in neuroscience research: the specialized analysis of astrocytic calcium events within fluorescence time-series imaging. Distinct from existing neuron-centric tools, astroCaST is adept at detecting and clustering astrocytic calcium events based on their unique spatiotemporal characteristics, thus filling a gap in astrocytic research methodologies. This toolkit not only facilitates the detection of such events but also extends its utility to provide comprehensive end-to-end analysis.This feature is absent in most tools targeting astrocytic activity. AstroCaST's development was motivated by the critical need for dedicated software that supports researchers in transitioning from raw video data to insightful experimental conclusions, efficiently managing large-scale datasets without compromising computational speed. It offers a user-friendly interface that caters to both novice and expert users, incorporating both a graphical user interface (GUI) for detailed explorations and a command-line interface (CLI) for extensive analyses. Expected outcomes from utilizing astroCaST include the ability to process and analyze a significantly larger volume of data. This enables a more profound and comprehensive analysis than previously possible, addressing the demands of large-scale astrocytic studies. In summary, astroCaST aims to advance astrocytic calcium imaging analysis, offering a tailored, efficient, and comprehensive toolset that enhances our understanding of astrocytic functions and their implications in neuroscience.